A comprehensive review on the assessment of fuel additive effects on combustion behavior in CI engine fuelled with diesel biodiesel blends. Issue 83 (9th September 2015) - Imdadul, H. K.; Masjuki, H. H.; Kalam, M. A.; Zulkifli, N. W. M.; Rashed, M. M.; Rashedul, H. K.; Monirul, I. M.; Mosarof, M. H.
<x xml:space="preserve">Abstract</x> Development in transport technology is a major issue owing to the increase the number of vehicles, which in turn increases emissions, which result in global warming.